Managing Movement of Returning Rice Straw into Soil (RRIS): A Solution to Land Degradation - Mimin Aminah; Muhammad Firdaus; Arief Hartono; Gelar Satya Budhi (Brawijaya University, 2022)
Concern on rice production in Indonesia is escalating since the production of rice tends to be levelling off for more than a decade. Soil degradation in lowland is among the main challenges. Soil encounters continuous decreasing organic matter and organic carbon content because the biomass from the rice plants was not returned to the land sufficiently. Most of the biomasses went out of the land or were burned by rice producers since there was not enough time to decompose the biomass before returning into the soil of lowland or it need additional cost to do so. Most farmers preferred to return the rice straw after burning, but it will not improve the condition. Otherwise, burning of rice straw caused air pollution since it released at least three kg particulate matter consisting of CO, SO2, CO2, and ash. Using interpretive structural modeling (ISM) this paper is trying to find the important factors with sequential solution. The result shows that encouraging rice producers to return rice straw into soil (RRIS) should start with Provision of Immediate Decomposing Technology and assistance program and Credit and Assistance Program.Keywords : managing soil degradation, organic matter, rice straw, ISM